Redu Cultural Elements and Characters of The Characters in the Play Novel Elephant Mada Oath in Manguntur Work Sky Kresna Hariadi - Sujoko Sujoko (Kognitif: Jurnal Pendidikan dan Inovasi Pembelajaran, 2026)
The purpose of this research is to describe the cultural elements and the characters in the novel "Gajah Mada Sampah di Manguntur" written by Langit Kresna Hariadi. The method of the research is analytical descriptive in which the process of analyzing and describing the main object of the research. Based on the analysis of the research, it can be concluded that the novel "Elephant Mada Oath in Manguntur" includes cultural elements, especially Javanese culture in the Majapahit Kingdom era. These matters can be seen from the structure of the event on the novel. The element of reliance towards many things such as belief in the power of dreams and belief in the power of magic are found in some sequences of the stories. Furthermore, the other element of culture can also be seen from this novel, such as information technology as an interesting fact in which the bird in the Majapahit era is used as a tool to deliver information. Moreover, another element of culture that is shown in this novel is the domination of elements of language. The characters appear in the The novel is divided into 5 (five) characters which are identified as strong characters, such as the character of Gajah Mada. While being a caring person, he also protects his country and the people who need protection. Besides, he can also work on a team in solving tasks. Moreover, the character of Elephant Enggon is also identified US a strong character in the novel. He is a mainstay who has a unique and deft character. Then, there is a Pradhabasu character who also has a unique character. Beside his good and nice character, his ability is in kanuragan (spiritual ability) is an interesting thing in this novel. The next character is Prabu Putri Dyah Wiyat who has an honest character which can be seen from her utterances in saying things with honesty in which she said that she was ever involved in a forbidden relationship.